2012
DOI: 10.1109/jsyst.2011.2165639
|View full text |Cite
|
Sign up to set email alerts
|

Robust Wide-Area TS Fuzzy Output Feedback Controller for Enhancement of Stability in Multimachine Power System

Abstract: This paper presents a systematic procedure for designing a wide-area centralized Takagi-Sugeno fuzzy controller to improve the angular stability of a multimachine power system. The proposed fuzzy controller is robust and designed by satisfying certain linear matrix inequality conditions, to stabilize the system at multiple operating points. The bilinear matrix inequality problem, encountered in Lyapunov-based stability criterion, has been converted into a convex optimization problem to eliminate iterative solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 23 publications
0
40
0
Order By: Relevance
“…A plenty of research has demonstrated the theoretical validity and practical availability of geometric and residue approaches to choose the most suitable wide-area feedback signal for POD [36][37][38]. In this study, the concept of joint modal controllability/observability index is adopted as wide-area feedback signals selection method to decouple modal interactions of multiple feedback signals [32].…”
Section: Selection Of the Wide-area Feedback Signalsmentioning
confidence: 99%
See 1 more Smart Citation
“…A plenty of research has demonstrated the theoretical validity and practical availability of geometric and residue approaches to choose the most suitable wide-area feedback signal for POD [36][37][38]. In this study, the concept of joint modal controllability/observability index is adopted as wide-area feedback signals selection method to decouple modal interactions of multiple feedback signals [32].…”
Section: Selection Of the Wide-area Feedback Signalsmentioning
confidence: 99%
“…A classical lead-lag type POD is adopted in this coordinated design strategy. The joint modal controllability/observability index is employed to choose the most appropriate wide-area feedback signals for PODs [32]. The coordinated design strategy is addressed as an eigenvalue-based optimization problem [33].…”
Section: Introductionmentioning
confidence: 99%
“…The classic PSS is connected to G 2 and G 3 based on and intelligent method presented in [28] to damp out local modes of oscillations. Then, the additional global signal is assumed to be provided to the stabilizer of the selected generator from a centralized wide In this test the critical mode is categorized in to two mode as; Mode one: −0.0046± 3.4279i eigen-value, 0.25% damping by 0.5456 (Hz) frequency, Mode one: −0.5297± 6.8076i eigen-value, 7.76% damping by 1.0835 (Hz) frequency [8].…”
Section: Two-area Four-machine Systemmentioning
confidence: 99%
“…To demonstrate the effectiveness of the proposed strategy, this method has been tested over three case studies through the comparison of without wide area controller and [8]. The simulation results have been tested in different load con-dition and faults where two scenarios have been considered to find the capability of the proposed wide area control strategy.…”
Section: Two-area Four-machine Systemmentioning
confidence: 99%
See 1 more Smart Citation